Low Temperature Microwave Assisted Hydrothermal Carbonization (Mahc) Reduces Combustion Emission Precursors in Short Rotation Coppice Willow Wood - Diaz-Robles, L (Elsevier B.V., 2018)
The combustion of biomass can be both CO2 neutral and economically beneficial. One major negative aspect are the gaseous and particle emissions that are formed by inorganic precursors in the biomass. These inorganic elements also cause slag formation. Short rotation coppice (SRC) willow wood contains a relatively large proportion of these precursors. This paper investigates the potential of low temperature Microwave Assisted Hydrothermal Carbonization (MAHC) for the reduction of emission precursors in SRC willow wood. Most of the respective elements were significantly reduced at the selected temperatures of 150 °C, 170 °C, and 185 °C. The most efficient combination of energy input, increasing heating value and decreasing mineral content was obtained at 170 °C. This shows the high potential of the MAHC treatment for utilizing low quality biomass as biofuel. © 2018 Elsevier B.V.